Development of pineapple (Ananas comosus) farming based on SWOT analysis: a case study in Baamang Hulu Village, Kotawaringin Timur Regency - Wahyuni, Wahyuni; Handayani, Leni; Pakpahan, Sartika (AGRICOLA, 2025)
Baamang Hulu Village, located in Kotawaringin Timur Regency, has great potential for the development of pineapple farming due to its favorable land conditions. However, farmers face various challenges, such as limited farm management, the use of simple technology, and market price fluctuations. This study aims to identify the internal and external factors influencing pineapple farming and formulate its development strategies. The research employs SWOT analysis with a descriptive qualitative approach, involving 30 pineapple farmers selected through simple random sampling. The results indicate that the strength factor score (2.33) is higher than the weakness score (0.61), while the opportunity score (2.65) exceeds the threat score (0.48), placing pineapple farming in a highly potential condition for development. The main supporting factors include seed availability, ease of cultivation, and farmers’ experience, whereas the biggest challenges are the lack of financial management and the absence of farmer groups. The recommended strategies include product diversification, strengthening farm management, utilizing technology and social media for promotion, and establishing partnerships with the government and marketing institutions. Implementing these strategies is expected to enhance the competitiveness and sustainability of pineapple farming.